Frontiers of creative industries : exploring structural and categorical dynamics - Jones, Candace; Maoret, Massimo (Research in the sociology of organizations ;, 2018)
Creative industries are a growing and globally important area for both economic vitality and cultural expression of industrialized nations. The growth and dynamism of creative industries depends on continuous innovation that must manage inherent tensions such as novelty to attract consumers and sustain artistic expression and familiarity to aid comprehension and stabilize demand for cultural products. In this volume, the macro-structural conditions that shape creative industries - their institutional, categorical and structural dynamics - are examined to provide an overview of new trends and emerging issues in scholarship on this topic. Creative industries offer products and services that range from the prosaic to the sublime and provide meaning to our lives, and this volume features a wide range of examples, from advertising, to architecture, art markets, Champagne wine, fashion and music. Contributors examine topics such as the micro-interactions of brokerage relations; how actors transform a brokerage role from control to co-production to enact creative leadership; how investors provide legitimacy to the new categories such as abstract art; how technological disintermediation creates alternative category processes such as authenticity; how social relations shape social evaluation; how prototypical producers can trespass categories and avert negative evaluation; how personal styles enable social evaluation; and how the ambiguity of a category, such as Swing music, facilitated its adaptability and longevity. The volume concludes with an Afterword examining research on creative industries as a form of cultural product and a category in itself.